Characteristics and Origin of Organic Matter in Triassic Lacustrine Shale From Fuxian Oilfield - Bojiang, Fan (Frontiers in Earth Science, 2021)
Along with the successful exploitation of shale oil, organic-rich shale has attracted great attention to the geologists. However, quantitatively differentiating the origin of organic matter in shale is still challenging due to the nature of its complex depositional processes. Organic matter in lacustrine shales could be derived from both lake water (produced by lake water column) and land input (transported into the lake by rivers). The Triassic Chang-7 shale in the Yanchang Formation is a typical lacustrine shale deposited in the central part of the Ordos Basin. It is rich in organic matter (TOC of 0.52−9.37%) and consists primarily of type II1 kerogen. The Chang-7 shale is thermally mature and currently in the stage of generating oil and gas, with more structured than organic matter. In this study, quantitative models of organic matter in the Chang-7 shale with sources from both lake water and land is established using geochemical and carbon isotopes data and the results show that lake water and land input have the almost equal contribution to the organic enrichment in the study area.